BIONOMIK Anopheles spp SEBAGAI DASAR PENGENDALIAN VEKTOR MALARIA DI KABUPATEN KEBUMEN JAWA TENGAH - Dhian Prastowo; Widiarti Widiarti; Triwibowo Ambar Garjito, S.Si, M.Kes (Balai Besar Penelitian dan Pengembangan Vektor dan Reservoir Penyakit (B2P2VRP) Salatiga, 2018)
Malaria is one of the serious diseases in Indonesia and is the target of Central Java Provincial Government in Malaria Elimination Program. One attempt to eliminated malaria is by knowing the vector bionomics, Anopheles spp as the basis of the policy control. The research was conducted in the location indicated by malaria case in Wagirpandan Village, Rowokele District Kebumen Regency. The study was conducted in two sampling sites, taking samples of adult mosquitoes and larvae. Environmental parameters observed include pH, temperature, rainfall and humidity and vegetation. The results of this study found seven species which were Anopheles aconitus, An. Annularis, Anopheles barbirostris, An. balabacencis, An. kochi, An. maculatus. An. vagus. The peak activity of the blood sucking of Anopheles spp around 08.00-09.00; 10.00-11.00 pm and 04.00 – 05.00 am outside the house and cattle pens. The proportions of parous mosquitoes are caught 42,8% in Cuntelan and 69,49% in Borang. All mosquito except An. Annularis and An. Kochi found were confirmed as malaria vectors.